The Role of The Internal Audit Management of Enterprise Risk Management - Siwidyah Desi Lastianti; Endang Muryani; Mahrus Ali (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
The aim of the study to present the role of internal audit in the company. The role of internal audit in the company is very important to control not only the financial sector but also other sectors that have been determined by the management. There is a relationship that is so tightly between the internal audit and corporate management, internal audit which can increase the value and achieve its goals. Internal audit should also adjust its function, not only on financial issues, but other problems, associated with risk and improved control strategies.